2012
DOI: 10.1039/c1dt11450f
|View full text |Cite
|
Sign up to set email alerts
|

The addition of amides to group 14 (di)-metallenes

Abstract: The addition of a series of primary and secondary amides to the group 14 (di)metallenes Mes(2)Si=SiMes(2), Mes(2)Ge=GeMes(2) and (Me(3)Si)(2)Si=C(OSiMe(3))R, where R = t-Bu or R = 1-Ad, was examined. In general, the addition of primary and N-methyl amides gave amide adducts whereas the addition of N-phenyl amides gave imidate adducts. The regiochemistry of the additions was highly dependent upon the substituent bonded to the amide nitrogen. We propose that the formation of the adducts proceeds by way of a zwit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…64 Single-crystal analysis shows the angle N-Si-Si to be 116.91 and Si-N and Si-Si bond lengths of 1.720 and 2.386 Å respectively, all consistent with the assignment of silicon(II). Similar structures for M(14)(IV) compounds are available from the reaction of R 2 M(14 14)M( 14) 0 R 2 H. Using N-phenyl amides, the products are R 2 {R 0 C(QNPh)O}M( 14)M( 14) 0 R 2 H. 65 This pattern of reactivity was proposed as a model for the interaction of germanium surfaces with amides.…”
Section: M(14)-m(14)mentioning
confidence: 78%
“…64 Single-crystal analysis shows the angle N-Si-Si to be 116.91 and Si-N and Si-Si bond lengths of 1.720 and 2.386 Å respectively, all consistent with the assignment of silicon(II). Similar structures for M(14)(IV) compounds are available from the reaction of R 2 M(14 14)M( 14) 0 R 2 H. Using N-phenyl amides, the products are R 2 {R 0 C(QNPh)O}M( 14)M( 14) 0 R 2 H. 65 This pattern of reactivity was proposed as a model for the interaction of germanium surfaces with amides.…”
Section: M(14)-m(14)mentioning
confidence: 78%
“…Dehydrogenative condensation of organosilanes and amines also represents one of the most attractive and atom-economical synthetic approach to access silylamines, an important class of silicon compounds that have been widely used as silylation agents, ligands for organometallic compounds, and precursors for Si and N polymeric materials . Both homogeneous and heterogeneous catalysts have been reported for this reaction, although control of the selectivity for Si–N coupling has proved to be challenging, as the reaction can lead to several products with different Si/N ratios (e.g., polysilazanes) as a result of multiple dehydrocoupling steps.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The photochemistry of catenated group 14 compounds is of interest since this method can be used to convert one type of catenate to another and also can be used for the generation of reactive intermediates including silylenes, germylenes, stannylenes, and group 14 element centered radical species that can be trapped and characterized . In the case of germanium, the photochemistry of the cyclotrigermane (Mes 2 Ge) 3 has been the most extensively studied and it has been shown that this compound is photochemically converted to a germylene Mes 2 Ge : and a digermene Mes 2 Ge=GeMes 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of germanium, the photochemistry of the cyclotrigermane (Mes 2 Ge) 3 has been the most extensively studied and it has been shown that this compound is photochemically converted to a germylene Mes 2 Ge : and a digermene Mes 2 Ge=GeMes 2 . The chemistry of both of these photoproducts has been thoroughly investigated , , , , , . However, only a few investigations into the photochemistry of linear oligogermanes have been described.…”
Section: Introductionmentioning
confidence: 99%